THE EFFECT OF CONTEXTUAL TEACHING AND LEARNING (CTL) LEARNING MODEL ON THE LEARNING OUTCOMES OF CREATIVE PROJECTS AND ENTREPRENEURSHIP OF CLASS XI STUDENTS OF HKBP PEMATANGSIANTAR PRIVATE VOCATIONAL SCHOOLS IN THE ACADEMIC YEAR 2024/2025 - Dony Wira Simbolon; Binsar Tison Gultom; Sotarduga Sihombing (RADJA PUBLIKA, 2025)
This study aims to determine the Effect of the Contextual Teaching and Learning (CTL) Learning Model on the Learning Outcomes of Creative Projects and Entrepreneurship of Class XI Students of HKBP Pematangsiantar Private Vocational Schools in the Academic Year 2024/2025. This study uses a pre-experimental research method of the one-group posttest-questionnaire type. Based on the partial hypothesis test, the results show that there is a positive and significant influence between Contextual Teaching and Learning (CTL) on learning outcomes as indicated by the t count (2.069)> t table (2.00324). Based on the determination coefficient test, the Rsquare value was obtained at 0.072, which means that 7.2% of the Contextual Teaching and Learning (CTL) variable influences the Learning Outcomes of Creative Projects and Entrepreneurship of Class While 92.8% is the influence of other variables that were not examined in this study.